Economic gangsters : corruption, violence, and the poverty of nations - Fisman, Raymond (Princeton University Press, 2010)
Meet the economic gangster. He's the United Nations diplomat who double-parks his Mercedes on New York City streets at rush hour because the cops can't touch him--he has diplomatic immunity. He's the Chinese smuggler who dodges tariffs by magically transforming frozen chickens into frozen turkeys. The dictator, the warlord, the unscrupulous bureaucrat who bilks the developing world of billions in aid. The calculating crook who views stealing and murder as just another part of his business strategy. And, in the wrong set of circumstances, he might just be you. In Economic Gangsters, Raymond Fis.